High performance carbon-based printed perovskite solar cells with humidity assisted thermal treatment. Issue 24 (2nd June 2017) - Hashmi, Syed Ghufran; Martineau, David; Dar, M. Ibrahim; Myllymäki, Teemu T. T.; Sarikka, Teemu; Ulla, Vainio; Zakeeruddin, Shaik Mohammed; Grätzel, Michael
Abstract : We report humidity assisted thermal exposure (HTE) as a post-treatment method for carbon based printed perovskite solar cells (CPSCs). Abstract : We report humidity assisted thermal exposure (HTE) as a post-treatment method for carbon based printed perovskite solar cells (CPSCs). The method does not only improve the interfaces of different layers of the printed stack, but also provides a pathway to fabricate high performance CPSCs with low hysteresis along with high stability. The HTE treatment directly influences over the associated components in the stack and remarkably improves each photovoltaic parameter of the CPSCs as seen by several characterization schemes presented in this study. The average initial efficiency (9.0% ± 0.2%) of the CPSCs of a batch was significantly improved to 13.1% ± 0.2% i.e. as high as 45% when subjected to HTE treatment for a period of 200 hours. Furthermore, the highest average efficiency obtained from the same batch from reverse scanning was 13.8% ± 0.4% with a CPSC attaining as high as 14.3% when exposed to the same thermo-humid environment for a period of 115 hours. Above all, the stability of the HTE treated CPSCs was also not compromised for over 350 hours under full-sun illumination stress testing at 40 °C. The results presented in this work provide an opportunity to adopt HTE treatment as a complementary step for the fabrication of high-performance carbon-based perovskite solar cells with low hysteresis accompanied by high durability and performance reproducibility.